Art therapy through the eyes of art teachers: a qualitative study of adolescents’ educational practices - Wu, Yumeng; Burhanuddin, Nur Aimi Nasuha (2024)
Art therapy activities have proven valuable in emotional expression, psychotherapy, cognitive development, and social interaction. However, at present in China, the popularity of art therapy is low, and teachers lack practical and theoretical experience as well as professional training in art therapy. Therefore, the purpose of this study was to explore art teachers' perceptions and challenges facing art therapy activities in school-based settings and provide insights into art teachers' professional training and policy making. This study utilized a qualitative case study to collect data through semi-structured interviews with three professional art teachers in a primary school in China. Thematic analysis was conducted in analyzing the research data. The main findings of the study showed that despite some challenges faced by the teachers, such as dealing with sudden changes in students' moods and a deep lack of knowledge about psychology, they had a positive attitude towards painting art therapy, and the participants described the art therapy activities as a release of stress, and activity for the unique expression of art. In future research, we encourage more schools and teachers at different grade levels to support art therapy activities for more age groups of youth to increase the representativeness and credibility of the study.